Problématique de la non-participation communautaire au processus d’aménagement des routes de dessertes agricoles pour un développement durable du territoire de Masisi. - Doctorant BAHATI NZABANITA Justin (IJRDO - Journal of Social Science and Humanities Research, 2024)
This paper focuses on community participation in the process of developing agricultural dessert roads for sustainable development in rural areas in Masisi territory. The question at the center of the study was in fact, to inventory the determining factors of community non participation in the process of developing roads in agricultural deserts for sustainable development in rural areas. That is to say, the causes of this non-participation, the consequences associated with it while considering the establishment of a strategy in terms of road rehabilitation program in the territory of Masisi with a view to improving conditions of the life of the population as a whole. After analyzing and processing the data using Word, Excel and SPSS, our research resulted in results according to which the causes of community non-participation in the process of developing agricultural feeder roads remain the abandonment of maintenance activities, the poor exploitation of roads and the associated consequences are: lack of employment, impoverishment of the entire population with rising food prices, rotting of products in the fields, and the absence of investors; which justifies the low contribution to local, regional, national and international development. Faced with this situation, a program to rehabilitate roads in agricultural deserts was put in place with a view to improving the socio-economic conditions of the population to finally lead to sustainable development.